Finite element analysis of lumbar spine - Fairul Idzwan, Mohd Rosni (2010)
Three-dimensional models of the one and two vertebrae were developed to clarify the mechanical cause of low back pain. The lumbar structures produced allowed the simulation by the performance of finite element analysis of different situation movement. The purpose of this study was to analyze the highest stress concentration on lumbar spine L1 and L2. However, little information is focused on the stress concentration on the axial compression and complex movement. This study stress concentration of the lumbar spine of L1-L2 by using the commercial software MSC Patran software for pre and post processor and MSC Nastran to solve the finite element analysis. Another scope is focus on 3D solid body of lumbar spine. Along with the increase in use of the finite element method has come a corresponding increase in its potential. There are several important keys to the proper application of any numerical method. The geometry, material properties and boundary condition is a technique to solve the finite element analysis that must have in finite element method. The loading conditions were that 450 N for axial compression and 150 N with 10 Nm for flexion, extension and lateral bending respectively were imposed on the superior surface and facet joints of the L1 vertebral body. The bottom of the L2 vertebral body was fixed in all direction completely. The variable meshing also been analyze of tetrahedral 10 and tetrahedral 4 this due to get optimize result on the analysis. In the starting position, the spines were found to be relaxed without any movement. As the axial compression been applied with increase of force the spine the displacement also will increases. The data have been compared with literature that seems good agreement for the result. Then flexion, extension and lateral been analyze to get the stress concentration since tetrahedral 10 is optimize to the geometry the analysis seen was found in pedicles, laminar and spinous processes on the Von mises stress as a parameter. From the research that can be conclude is the finite element analysis has the same result with the experiment that can compare with other journal. It also can be help in the clinical to cure the patients. It easy to know which part injured happen in lumbar spine and why.